The Relation of Night-Hypoxia with Otolith Dysfunction in patient suffering from Sleep Apnea - Bashir Ahmad, Asmatullah, Habibullah (Pakistan Journal of Medical & Health Sciences, 2025)
Objective: To evaluate the relation of night hypoxia with the otolith dysfunction in patients suffering from sleep apnea. Study design: Prospective study Place and duration of study: Department of ENT Head & Neck Surgery, Bolan Medical College, Quetta from 1st April 2023 to 30th September 2023. Methodology: Sixty patients attended cardiorespiratory polysomnography (PSG) with sleep apnea and age group of 24 to 75 years were enrolled. All the cases were assessed for various sleep parameters including Apnea hypopnea Index, horizontal Video Head Impulse Test Results (vHIT) as well as the Vestibular function was assessed using video head impulse test of horizontal evaluating semicircular canal function and cervical vestibular evoked myogenic potentials (cVEMPs) and ocular vestibular evoked myogenic potentials (oVEMPs) to measure otolith function cVEMP and ocular VEMPs (oVEMP). Head and eye movement was assessed using a high-speed infrared camera at 250 Hz. The vestibular-ocular reflex (VOR) was also assessed. All these parameters were used for evaluating the relation of night hypoxia with otolith dysfunction in patients with sleep apnea. All the information, including the demographic details, BMI as well as clinical history was noted. Results: There was a significant majority of males (76.6%). The apnea hypopnea index was calculated, and it was observed that 21 (40%) were in the index range of ≥ 30 showing severity level. There were higher cases of diabetes in AHI 15 ≥ x <30 while more patients with hypertension (n=12) were identified to have more severe levels of AHI such as >30. A strong association was found between AHI, vHIT with diabetes and hypertension especially in cases where AHI ≥30. The frequency of hypertension was highest in cases with AHI greater or equal to 30. Diabetes was minimally present in control cases wherein the OSA was not presented with an AHI level <5. In this context the descriptive indices, there were more cases of diabetes and hypertension with pathological VEMP. There was no significant association found between the sleep parameters and vestibular functions. Conclusion: There was no significant association between vestibular function and sleep apnea, although otolith dysfunction was significantly presented in cases of obstructive sleep apnea and hypertension. Keywords: Night hypoxia, Otolith dysfunction, Sleep apnea, Relation.